2008
DOI: 10.1158/1078-0432.ccr-07-4926
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Controls Flat Dysplastic Aberrant Crypt Foci Development and Colon Cancer Progression in the Rat Azoxymethane Model

Abstract: Purpose: Colonic carcinogenesis deranges growth-regulating epidermal growth factor receptors (EGFR). We previously showed that EGFR signals were up-regulated in human aberrant crypt foci (ACF), putative colon cancer precursors. The azoxymethane model of colon cancer recapitulates many aspects of human colonic tumors. Recent studies indicate that flat dysplastic ACF with increased h-catenin are tumor precursors in this model. We asked, therefore, if EGFR signals are required for flat dysplastic ACF development … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 50 publications
3
49
0
Order By: Relevance
“…21,[32][33][34] On the other hand, increased COX-2 has been documented in large or flat dysplastic AOM-induced ACF. 35,36 In agreement with these latter reports, we also found a modest, but significant increase in COX-2 expression in ACF. Importantly, when analysing MDF, that we consider the precursor lesions of colon cancer, we found a strong increase in COX-2, higher than that found in ACF or tumours.…”
Section: Discussionsupporting
confidence: 92%
“…21,[32][33][34] On the other hand, increased COX-2 has been documented in large or flat dysplastic AOM-induced ACF. 35,36 In agreement with these latter reports, we also found a modest, but significant increase in COX-2 expression in ACF. Importantly, when analysing MDF, that we consider the precursor lesions of colon cancer, we found a strong increase in COX-2, higher than that found in ACF or tumours.…”
Section: Discussionsupporting
confidence: 92%
“…This finding raises the question of the in-vivo mechanism(s) by which curcumin may have cancer-preventive effects in the setting of early pre-invasive neoplastic lesions. Potential mechanisms may involve down-regulating different signaling cascades such as epidermal growth factor receptor (EGFR) or insulin-like growth factor receptor (IGFR) signaling, either of which has been linked to ACF formation (38, 39) and is known to be inhibited by curcumin in cell-culture models (40). Alternatively, curcumin may act via influencing Notch signaling, as shown in pancreatic cell lines (41), and Wnt signaling, as shown in breast-cancer stem cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies we demonstrated that EGFR signals play a critical role in colonic tumorigenesis (6, 48, 49). The AT1 receptor can transactivate EGFR (24).…”
Section: Discussionmentioning
confidence: 92%
“…Prior studies showed that EGFR promotes colonic tumor development, whereas vitamin D inhibits tumorigenesis in models of colon cancer (6, 8, 32, 47-49). To examine how VDR alters colonic tumorigenesis and EGFR signals, we treated Vdr −/− and Vdr +/+ mice with AOM/DSS.…”
Section: Discussionmentioning
confidence: 99%